Direct economic losses in farms and government compensation costs due to highly pathogenic avian influenza outbreaks in Japan during the 2022–23 season - UKITA, Makoto; YASUDA, Ayaka; KIKUCHI, Eisaku; HINATA, Takahisa; MAKITA, Kohei (Journal of Veterinary Medical Science, 2025)
Highly pathogenic avian influenza (HPAI) is a contagious disease of poultry characterized by high avian mortality and devastating economic losses. Between October 2022 and April 2023 (in the 2022–23 season), there were 84 cases of HPAI on poultry farms in 26 prefectures of Japan, resulting in the culling of approximately 17.7 million birds. This study examined the economic impact of HPAI outbreaks on poultry farms in Japan during the 2022–23 season. Farm direct economic losses and burden to the national and prefectural governments from compensation were estimated. Data were obtained from epidemiological survey reports prepared by the Ministry of Agriculture, Forestry and Fisheries, prefecture websites, and through direct contacts. Losses incurred by the national government as compensation granted to infected farms for birds culled and eggs discarded as contaminated goods were estimated. Economic losses for poultry farms located in movement and shipment restriction zones were assumed to be reduced sales and increased farm management costs and shared equally by the national government and infected prefectures. Economic losses on infected farms were estimated from the outbreak until recovery of production. Total economic losses incurred by the national government, infected prefectures, and infected poultry farms were estimated at approximately 16.9 billion, 183.5 million, and 14.2 billion Japanese yen (USD 126.6 million, 1.4 million, and 106.4 million), respectively. Although data are limited, the quantification of economic losses due to HPAI in this study could contribute to future evidence-based policy making.